2007
DOI: 10.1352/0895-8017(2007)112[18:stseca]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Setting the Stage: Early Child and Family Characteristics as Predictors of Later Loneliness in Children With Developmental Disabilities

Abstract: Children with developmental disabilities often report having few friends. Researchers have tended to focus on social skill deficits, neglecting other potent predictors of children's feelings of loneliness. In a sample of 82 children with developmental disabilities, we examined characteristics of the child at age 3 (i.e., the conclusion of early intervention services) as well as family income and emotional climate as predictors of children's reported feelings of loneliness at school during middle childhood (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…A review reported that 10%-15% of the children and adolescents felt very lonely 7 . It was shown that various factors such as the quality of the social relations were significantly correlated with development of loneliness experience in children and adolescents 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…A review reported that 10%-15% of the children and adolescents felt very lonely 7 . It was shown that various factors such as the quality of the social relations were significantly correlated with development of loneliness experience in children and adolescents 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that students with disabilities, such as mild intellectual disabilities, learning disabilities, and autism in inclusive settings reported more loneliness and less satisfaction in peer relationships compared to their typically developing peers (Heiman & Margalit, 1998;Jobe & White, 2007;Pavri & Luftig, 2001;Pavri & Monda-Amaya, 2000;Valas, 1999;Williams & Asher, 1992). However, a limited number of studies have examined the relationships between loneliness and self-concept (Fujiki, Brinton, & Todd, 1996), loneliness and social skills (Zeedyk, Cohen, Eisenhower, & Blacher, 2015), and loneliness and problem behaviors (Howell, Hauser-Cram, & Kersh, 2007). Moreover, only a few studies in Turkey have investigated the academic achievements and social and behavioral characteristics of SEN students in inclusive classrooms (Girli, 2013;Kanay & Girli, 2008;Sucuoglu & Ozokcu, 2005), and no studies have focused on the relationship of loneliness with self-concept, social skills, or problem behaviors of children with special needs except one study examined the relationship between the loneliness and social status of SEN students (Bakkaloglu, 2010).…”
mentioning
confidence: 99%
“…In general, studies indicate that young children with Down syndrome have comparatively small peer social networks as well as less well developed linkages with peers across settings, exhibit a general absence of reciprocal friendships, and report high levels of loneliness (Byrne, Cunningham, & Sloper, 1988; Carr, 1995; Freeman & Kasari, 2002; Guralnick, 2002; Guralnick, Connor, & Johnson, 2009; Howell, Hauser-Cram, & Kersh, 2007; Sloper, Turner, Knussen, & Cunningham, 1990). …”
mentioning
confidence: 99%